Uptake of indolmycin in gram-positive bacteria. - Werner, R G (1980)
The antimicrobial activity of indolmycin correlates with the generation time of the investigated strains. Thus, in Staphylococcus aureus ATCC 13150 with a 37-min generation time, the minimal inhibitory concentration (MIC) was 0.6 microgram ml-1, and in Bacillus subtilis ATCC 27142 with a generation time of 23 min, the MIC reached 10.5 micrograms ml-1. Competition experiments in staphylococci and B. subtilis with aromatic amino acids demonstrated that indolmycin uses the uptake systems that are responsible for tryptophan. When the Ki values of indolmycin for the uptake of the aromatic amino acids in staphylococci were compared, there was a significantly higher influence on the uptake of tryptophan with respect to phenylalanine and tyrosine. In addition, indolmycin low resistant mutants of S. aureus ATCC 13150 showed a 10- to 100-fold decrease in Km value for the uptake of tryptophan and a 10-fold decrease for tyrosine uptake. The Km value for phenylalanine remained unchanged. A significant correlation existed between the Ki values of indolmycin for the uptake of tryptophan in the wild-type strains of S. aureus and B. subtilis and the MIC against the corresponding strain. Low Ki values corresponded to low MIC. These results imply that, in addition to improvement of the antibiotic structure for target affinity, the tryptophan uptake system can be used as a test model for the structural evaluation of indolmycin with respect to an increased transport activity into bacterial cells.